2018
DOI: 10.1080/13510002.2018.1445581
|View full text |Cite
|
Sign up to set email alerts
|

Taurine alleviates endoplasmic reticulum stress in the chondrocytes from patients with osteoarthritis

Abstract: Osteoarthritis (OA), characterized by pain and stiffness, swelling, deformity and dysfunction of joints, affects large numbers of population. The purpose of this study was to discover the effects of taurine in human OA chondrocytes and explore the underlying mechanisms. 46 patients with different grades of OA were recruited. Of these patients, 24 underwent total knee replacement and cartilages were harvested. The mRNA expressions of type II collagen (Collagen II) and endoplasmic reticulum (ER) stress markers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…24 Taurine had cytoprotective effects on H 2 O 2 -stimulated chondrocytes via suppressing ER stress. 12 5,7,3 0 ,4 0 -tetramethoxyflavone had chondroprotective roles via blocking ER stress-mediated apoptosis. 25 Moreover, recent studies already proved the regulatory activities of baicalin on ER's function.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…24 Taurine had cytoprotective effects on H 2 O 2 -stimulated chondrocytes via suppressing ER stress. 12 5,7,3 0 ,4 0 -tetramethoxyflavone had chondroprotective roles via blocking ER stress-mediated apoptosis. 25 Moreover, recent studies already proved the regulatory activities of baicalin on ER's function.…”
Section: Discussionmentioning
confidence: 98%
“…The culture of human OA chondrocytes was performed via a previously reported method. 12 We subdivided chondrocytes into 5 groups: control group, H 2 O 2 group (incubation with 0.5 mM H 2 O 2 for 4 hours at day 4), H 2 O 2 + baicalin group (pretreatment via 100 μM baicalin for 1 day before H 2 O 2 administration), H 2 O 2 + baicalin + Tm group (pretreatment with 2.5 μg/mL Tm and 100 μM baicalin for 1 day before H 2 O 2 treatment) and H 2 O 2 + baicalin + TUDCA group (pretreatment with 100 μM TUDCA and 100 μM baicalin for 1 day before H 2 O 2 treatment).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, occurrence of ER stress has been demonstrated in chondrocytes of osteoarthritis cartilage in humans [ 12 , 13 ]. Increased levels of GRP78, PDI, CHOP, and caspase-12 have been detected in articular cartilage of OA patients, indicating the role of ER stress and ER stress-mediated apoptosis in OA progression [ 13 , 16 ]. Nevertheless, pathological events accompanying OA development are not the only ones causing ER stress in cartilage tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological inhibition of ER stress responses by repurposing an antiepileptic drug carbamazine is being trialled as a therapy for metaphyseal chondrodysplasia type Schmid [ 69 ]. In vitro studies on chondrocytes have suggested markers such as peptides from Col II synthesis and ER stress markers (GRP78, CHOP/GADD153 and Caspase12) are reduced with the exposure to amino acids such as taurine or the flavonoid baicalin that target the H 2 O 2 induced pathway [ 70 , 71 ]. GRP 78 is the master regulator of the unfolded protein response.…”
Section: Introductionmentioning
confidence: 99%